Exploring the views of academic staff on HIV/AIDS integration into the curricula: a case study of the University of Fort Hare - Zukiswa Theodorah Dasheka; Nomzamo Dube; Lulekwa Baleni; Eunice Seekoe; Actor Katurura; Nombulelo Lubisi; Daniel Ter Goon (Taylor & Francis Group, 2021)
As a clarion call by Higher Education HIV/AIDS programme (HEAIDS) to South African universities, entrenching, integration and infusing the teaching and learning of HIV/AIDS in the curriculum of universities prove to be a sustainable solution to changing risky behaviour and attitudes of university students towards HIV/AIDS. The majority of students in South African universities lack general awareness and education in HIV/AIDS. This raises the need to produce graduates who are knowledgeable and have a positive attitude regarding HIV/AIDS. A pilot study on HIV/AIDS curriculum integration at the University of Fort Hare involved academic staff was done. A qualitative case study approach was used to describe the process and effectiveness of the curriculum integration process. The data collection was through evaluation forms, reports and a focus group interview. Data were analysed using content analysis. Guskey's model for professional development was followed to understand the process and effect of curriculum integration. Initially, the academic staff anticipated that the HIV/AIDS curriculum integration process would result in credit overload for students, time constraints and increased workload. Later, most academic staff affirmed the benefits of being involved in the project such as improving teaching and facilitation styles and research.